CD137 Costimulation Enhances the Antitumor Activity of Vγ9Vδ2-T Cells in IL-10-Mediated Immunosuppressive Tumor Microenvironment - Pei, Yujun; Xiang, Zheng; Wen, Kun; Tu, Chloe Ran; Wang, Xiwei; Zhang, Yanmei; Mu, Xiaofeng; Liu, Yinping; Tu, Wenwei (Frontiers in Immunology, 2022)
Although γδ-T cell-based tumor immunotherapy using phosphoantigens to boost γδ-T cell immunity has shown success in some cancer patients, the clinical application is limited due to the rapid exhaustion of Vγ9Vδ2-T cells caused by repetitive stimulation from phosphoantigens and the profoundly immunosuppressive tumor microenvironment (TME). In this study, using a cell culture medium containing human and viral interleukin-10 (hIL-10 and vIL-10) secreted from EBV-transformed lymphoblastoid B cell lines (EBV-LCL) to mimic the immunosuppressive TEM, we found that the antitumor activity of Vγ9Vδ2-T cells was highly suppressed by endogenous hIL-10 and vIL-10 within the TME. CD137 costimulation could provide an anti-exhaustion signal to mitigate the suppressive effects of IL-10 in TME by suppressing IL-10R1 expression on Vγ9Vδ2-T cells. CD137 costimulation also improved the compromised antitumor activity of Vγ9Vδ2-T cells in TME with high levels of IL-10 in Rag2-/- γc-/- mice. In humanized mice, CD137 costimulation boosted the therapeutic effects of aminobisphosphonate pamidronate against EBV-induced lymphoma. Our study offers a novel approach to overcoming the obstacle of the hIL-10 and vIL-10-mediated immunosuppressive microenvironment by costimulating CD137 and enhancing the efficacy of γδ-T cell-based tumor therapy.